Strategi Manajemen Konflik Dalam Meningkatkan Produktivitas dan Kreativitas Organisasi - Siti Ma’unatul Afifah; Kanzul Aras Nurjannah; Septa Muhammad Royhan; Nur Fajrin Marsella Putri; Mu’alimin Mu’alimin (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Conflict management is an important aspect in organizations, including educational institutions, to create a harmonious and productive work environment. This research aims to understand the concept of conflict management, sources of conflict in organizations, and their impact on productivity and creativity. The method used in this research is a literature study, which examines various primary and secondary reference sources such as books, journal articles, and previous research relevant to the topic. The research results show that conflict in organizations can arise due to differences in goals, values or thoughts between individuals or groups. Conflict that is not managed well can reduce productivity and work quality, but if managed effectively, conflict can increase communication, creativity and innovation. There are various strategies in conflict management, such as avoidance, accommodation, compromise, collaboration and competition, which can be adapted to the context and characteristics of the conflict that occurs. Good conflict management can strengthen relationships between organizational members and support the achievement of common goals. Therefore, a deep understanding of conflict management is very important in increasing organizational productivity and creativity.